A broad survey of DNA sequence data simulation tools. (23rd December 2019) - Alosaimi, Shatha; Bandiang, Armand; van Biljon, Noelle; Awany, Denis; Thami, Prisca K; Tchamga, Milaine S S; Kiran, Anmol; Messaoud, Olfa; Hassan, Radia Ismaeel Mohammed; Mugo, Jacquiline; Ahmed, Azza; Bope, Christian D; et al.
Abstract: In silico DNA sequence generation is a powerful technology to evaluate and validate bioinformatics tools, and accordingly more than 35 DNA sequence simulation tools have been developed. With such a diverse array of tools to choose from, an important question is: Which tool should be used for a desired outcome? This question is largely unanswered as documentation for many of these DNA simulation tools is sparse. To address this, we performed a review of DNA sequence simulation tools developed to date and evaluated 20 state-of-art DNA sequence simulation tools on their ability to produce accurate reads based on their implemented sequence error model. We provide a succinct description of each tool and suggest which tool is most appropriate for the given different scenarios. Given the multitude of similar yet non-identical tools, researchers can use this review as a guide to inform their choice of DNA sequence simulation tool. This paves the way towards assessing existing tools in a unified framework, as well as enabling different simulation scenario analysis within the same framework.